Cultural Aspects of Criminal Responsibility - Shulman, Harry Manuel (The journal of criminal law, criminology and police science, 1952)
The classical theory of jurisprudence that criminal responsibility is a matter of knowing right from wrong had its origin in a simpler society in which it was possible for an individual to be, in the words of Tarde, identical with his culture. Cultures were relatively consistent in their values, and the monolithic pressures of relatively uniform culture values concealed the fact to the philosopher that human behavior was no rational outcome of the awareness of right and wrong conduct, but a product of an equilibrium between the individual and his society, in which the struggle for individual and group survival determined means to ends